Yu-Gi-Oh. Vol. 3, Capsule monster chess - Takahashi, Kazuki, 1961- (Shonen Jump graphic novel, 2003)
Contains several "Shonen Jump" adventures, including a showdown between Yugi and the Egyptian mystic Shadi, which decides the life or death of Yugi's best friends.